Gout : methodical recommendations for the preparation of students of higher education in the 5th year of study in the discipline «Internal medicine. Module of Internal medicine» - Тихонова, Тетяна Михайлівна; Горшунська, Мар’яна Юріївна; Аль-Травнех, Олена Володимирівна; Tykhonova, Tetiana M.; Gorshunska, Maryana Yu.; Al-Trawneh, Olena (Харків : Харківський національний університет імені В.Н. Каразіна, 2024)
Methodical recommendations outline the importance of uric acid metabolism in thepa hogenesis of gout, provide modern international definitions and classifications, consider the features of etiology and pathogenesis, clinical picture, diagnosis and treatment of gout. For students of the 5th year to prepare for practical classes in the discipline «Internal medicine. Module of Internal medicine».
Подагра (англійською мовою)
Keywords: подагра; гіперурикемія; сечова кислота; діагностика; лікування; уратзнижуючі засоби; gout, hyperuricemia; uricacid; diagnosis; treatment; urate-reducingtherapy; MEDICINE::Internal medicine::Rheumatology